Evaluation of Four Commercial Anti - Infectious Bursal Disease (IBD) Vaccines under Sudan Conditions - Babiker, M.A.A.; Yahia, I.E.; Noura, K.; Manal, M.E. (International Journal of Poultry Science, 2008)
The potency of four anti-infectious bursal disease vaccines commercially available in Sudan was evaluated. For this purpose 125 layer chicks were divided into five groups of 25 birds each. Group A, B, C and D were vaccinated with 228E, D78, Bio-Gumboro and Gumboro3 strain vaccines respectively. 228E strain is a hot vaccine while the rest are intermediate strain vaccines. While group E remain without vaccination and acted as a negative control Vaccination for each group was done twice at day 21 and 28 via drinking water route. ELISA test performed 15 days later revealed that vaccination using 228E vaccine induced the highest antibody titre and protected birds challenged at day 43 from clinical disease, postmortem gross lesions and mortality. In contrast birds vaccinated with Gumboro3 vaccine induced the lowest antibody titre. All vaccines used in the present study, except 228E vaccine, failed to protect birds fully from clinical signs, postmortem gross lesions and mortality caused by artificial challenge. The mean antibody titre of different groups was; 12521±2014.14, 4790±1234.95, 9903±966.91 and1587±824.80 and the mortality rate was 00%, 40%, 12% and 40% for group A, B, C and D respectively compared to antibody titre of 363±196.22 and mortality rate of 64% for the control group.